Ciência como montagem, montagem como ciência - Fontes, Carlos Henrique Lisboa (2006)
The thesis describes parallel possibilities between the knowledge built in theatre and in Science. The narrative is constructed through a reflexive observation of the process of making a threatical play, specifically O Tempo da Chuva by Grupo Beira de Teatro , in analogy to the process of making a scientific theory, specifically the one described by Werner Heisenberg in his book Physics and Beyond: encounters and conversations . It sets a dialog with authors/actors from various areas of knowledge, such as Edgar Morin, Werner Heisenberg, René Descartes, Paul Feyerabend, Paul Caro, Juremir Machado da Silva, Maria da Conceição de Almeida, Renato Ferracini, among others. It discusses the hypothesis that Science is the process of building and the theatrical process of building a play can also be systematized, likewise science. The thesis defends, as the complexities science may suggest, a method as a strategy. Developed throughout the process, such method could only be verified at the end, when the elements of the setting of atomic physics theories and theatre were correlated. Questions such as: the place of theatre and science in our contemporary society and the political and ethical role of artists and scientists are at the episthemological basis of this narrative which we have started, but it is not even close to a conclusion